Durable press finish with quality reference for cotton, viscose rayon and their blends with polyester / Salmiah Mohd. Nor - Mohd. Nor, Salmiah (2010)
In the preliminary study of Durable Press finish, ten new formulations of DPI to DPIO were applied on light weight cotton fabric, by the pad-dry-cure method in the laboratory. The finishing solution consisted of Durable Press agent containing the alkyl modified dihydroxy ethylene urea/melamine formaldehyde derivative, magnesium chloride, acetic acid and two softeners of functional polysiloxane active groups. The fabric was impregnated into the solution, padded and dried at 135°C for 30 minutes. Then it was cured at 140°C for five minutes. The finished fabric was tested and analyzed statistically for weight, wrinkle recovery angle (WRA), appearance, stiffness, drapability, abrasion resistance, breaking strength and tearing strength to decide on four formulations for trial run in the manufacturing process at the textile mill. The selected formulations with good Durable Press performances were DP7, DP8, DP9 and DPIO. These formulations were applied on four fabrics of light and medium weight cotton and polyester/cotton (65/35) after dyeing. At the mill, the formulations and application method of DP7, DP8, DP9 and DPIO, were the same as in the preliminary study, with an additional process of compressive shrinkage after curing. The finished fabrics were analyzed to decide on ONE optimum formulation of Durable Press finish, which was then applied on four other fabrics of light and medium weight viscose rayon and polyester/viscose rayon (65/35). This ONE formulation was DPIO, and it now becomes the Durable Press formulation for all eight fabrics.